(untitled) (The Shivapuri Journal, 2026)
Command appointment in military is a great opportunity which comes with many challenging responsibilities. Among many responsibilities of the commander, legal responsibilities are one of the most imperative ones, which are closely related to the legality and authenticity of the command tasks as well. Operational effectiveness of a military unit and sub-unit to a great extent relied on its leader or the commander. To become a good commander, one must have highest level of moral character and sense of duty in him first and should establish him as a role model in the unit. In this article, major legal responsibilities of the military commander, while serving in the unit of the Nepali Army, have been highlighted and critically analyzed with more focus on judicial, managerial, financial and command responsibilities. For this, concerned legal framework and recent practices have been considered and concluded that the commanders play vital role in management and professional competencies of any military unit and sub-unit.